Reformulating the principle of legality in the 2023 criminal code: legal certainty versus living law - Darwin Steven Siagian (Indonesian Institute For Counseling, Education and Therapy, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code signifies a paradigm shift in the national criminal law system from a rigid model of legal certainty based on lex scripta and lex stricta toward a more flexible approach to criminal law enforcement. Nevertheless, the recognition of the “living law in society” (living law) under Article 2 of the 2023 Criminal Code gives rise to constitutional concerns regarding the consistency of the formal principle of legality. This study aims to critically examine the implications of the reformulation of the principle of legality in the 2023 Criminal Code and to analyze the potential erosion of legal certainty resulting from the ambiguity surrounding the operational parameters of living law. The research employs a normative juridical method through statutory and conceptual approaches, supported by qualitative analysis of secondary legal materials to assess the harmonization between Article 1 and Article 2 of the 2023 Criminal Code. The findings indicate that the recognition of living law generates a contradictory dualism within the principle of legality. On the one hand, it is oriented toward achieving substantive justice; on the other hand, it creates opportunities for judicial arbitrariness and disparities in the application of law across regions. This condition reflects a tendency toward the obscuration of the principle of nullum crimen sine lege praevia, which consequently creates uncertainty in determining criminal acts and potentially weakens the protection of human rights against arbitrary criminalization. Therefore, the reformulation of the principle of legality in the 2023 Criminal Code may be regarded as an insufficiently mature compromise between legal modernization and the recognition of local values, thereby risking the sacrifice of legal certainty. Accordingly, more restrictive implementing regulations are required to limit the scope of the application of living law in order to ensure its conformity with the principles of the rule of law.